2022
DOI: 10.2196/36377
|View full text |Cite
|
Sign up to set email alerts
|

Quality Evaluation of Free-living Validation Studies for the Assessment of 24-Hour Physical Behavior in Adults via Wearables: Systematic Review

Abstract: Background Wearable technology is a leading fitness trend in the growing commercial industry and an established method for collecting 24-hour physical behavior data in research studies. High-quality free-living validation studies are required to enable both researchers and consumers to make guided decisions on which study to rely on and which device to use. However, reviews focusing on the quality of free-living validation studies in adults are lacking. Objective … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 259 publications
0
6
0
Order By: Relevance
“…Our study advances this aspect of open science in the measurement of sedentary time by including our analysis program for researchers to derive detailed sedentary postures. As described in detail within existing reviews on the topic [ 30 , 31 , 32 ], the validity of monitors to detect sedentary positions is important and well documented, but researchers may be interested in sitting time specifically. Our provided analysis program helps address this gap and provides researchers with the capacity to isolate sitting time from lying time, which may be useful for developing activity monitoring devices and/or validating sitting-time questionnaires.…”
Section: Discussionmentioning
confidence: 99%
“…Our study advances this aspect of open science in the measurement of sedentary time by including our analysis program for researchers to derive detailed sedentary postures. As described in detail within existing reviews on the topic [ 30 , 31 , 32 ], the validity of monitors to detect sedentary positions is important and well documented, but researchers may be interested in sitting time specifically. Our provided analysis program helps address this gap and provides researchers with the capacity to isolate sitting time from lying time, which may be useful for developing activity monitoring devices and/or validating sitting-time questionnaires.…”
Section: Discussionmentioning
confidence: 99%
“…In line with our previous reviews [ 47 49 ] about the quality of validation studies, we identified a large number of different research and commercial-grade wearables that were validated under laboratory conditions. The quality of a validation study is a highly critical criterion to enable both researchers and consumers to make a guided decision about which studies to rely on and which device to use.…”
Section: Discussionmentioning
confidence: 99%
“…The high BMI (30.57 +/− 6.32 kg*m −2 ) was particularly noticeable. The quantity and quality of sleep can change profoundly across the lifespan [ 49 , 94 ]. Older people commonly have difficulty falling asleep and staying asleep.…”
Section: Discussionmentioning
confidence: 99%
“…Results in the literature show a variable accuracy (moderate to good) of the wrist-worn activity trackers. Most of the research has been carried out on healthy young subjects [ 6 , 48 , 49 ]. A study of middle-aged to older sleep patients, patients with an average BMI in the obesity range, and patients with sleep disorders or sleep apnea and the isolated usage of nocturnal breathing aids, such as Continuous Positive Airway Pressure (CPAP) devices, can provide an extended view of the accuracy under these conditions.…”
Section: Introductionmentioning
confidence: 99%